Adherence to Diet and Exercise Regimen among Patients with Type 2 Diabetes Mellitus at the Tema General Hospital, Greater Accra, Ghana. - Wornyoh, G.D. (University of Ghana, 2020)
Background: Diabetes is not curable. Lifestyle changes such as diet and physical exercise are important factors in achieving good control of type-2 diabetes (T2D) thereby avoiding its long-term complications. However, knowledge on the factors that hinder the adherence to diet and physical exercise in diabetes management is limited. This study aimed to determine the adherence to dietary and exercise requirements among type 2 diabetics in the Tema General Hospital Method: A cross-sectional design was used in the study. Consecutive sampling was used to sample 275 patients who met criteria. A closed ended questionnaire was used to collect the data. Chi-square was used to assess relationships between variables. Simple logistic regression was used to test the study‟s hypothesis. Results were reported as odds ratios with 95% confidence intervals. Results: Adherence to dietary recommendations was 26.7%. Low socio-economic status of participants did not influence adherence to dietary and physical exercise recommendations. Participants on insulin only, (AOR=44.0; 95% CI=1.65- 1171; p=0.024). and those who were on drug and diet therapy, (AOR=55.3; 95%CI=5.59 – 547.6; p=0.001) were adherent to dietary recommendations. Participants who were not on herb therapy were less likely to be adherent to dietary recommendations (AOR= 0.002; 95%CI=0.001- 0.05; p<0.001). 67.8% of respondents were knowledgeable on the benefits of physical education and diet recommendations for diabetes management. Adherence to physical exercise recommendations was found to be 22%. Senior secondary school trained participants are less likely to adhere to exercise recommendations (AOR=0.01; 95%CI=0.001– 0.14; p= 0.004). Vocationally trained participants were less likely to be adherent to dietary recommendations (AOR=0.06; 95%CI=0.001-0.36; p<0.001). Participants who were knowledgeable about their condition were likely to be adherent (AOR=38.8; 95%CI=3.01- 49.25; p=0.016). 96% of participants had the recommended 3 square meals a day. Conclusion: Adherence to diet and exercise was found to be relatively low. The type of treatment and being on herb therapy was found to influence adherence to dietary recommendations. Majority of participants were knowledgeable about their condition
MPH.
Keywords: Diet; Physical Exercise; Type 2 Diabetes; Tema General Hospital; Greater Accra